International trade and determinants of price differentials of insulin medicine - Matthias Helble; Toshiaki Aizawa (Asian Development Bank Institute (ADBI), 2015)
Empirical studies on pharmaceuticals pricing across countries have found evidence that prices vary according to per capita income. These studies are typically based on survey data from a subset of countries and cover only one year. In this paper, we study the international trade and price of insulin by using detailed trade data for 186 importing countries from 1995 to 2013. With almost 12,000 observations, our study constitutes the largest comparative study on pharmaceutical pricing conducted so far. The large dataset allows us to uncover new determinants of price differentials. Our analysis shows that the international trade of insulin increased substantially over this time period, clearly outpacing the increasing prevalence of diabetes. Using the unit values of imports, we also study the determinants of price differentials between countries. Running various panel regressions, we find that the differences in prices across countries can be explained by the following factors: First, corroborating earlier studies, we find that per capita GDP is positively correlated with the unit price of insulin. Second, the price of insulin drugs originating from Organisation for Economic Co-operation and Development countries tends to be substantially higher than for those imported from developing countries. Third, more intense competition among suppliers leads to lower insulin prices. Fourth, higher out-of-pocket payments for health care are associated with higher prices. Finally, higher volumes and tariffs seem to result in lower unit prices.
Keywords: F14; I11; 330; Insulin trade; price differentials; pharmaceuticals trade